Skrining Fitokimia Hasil Ekstraksi Bertingkat Daun Jengkol (Archidendron jiringa) dan Aplikasinya Sebagai Zat Antijamur: Phytochemical Screening of Jengkol Leaf (Archidendron jiringa) Sequential Extraction Result and Its Application for Antifungal Agent - Mohammad Jihad Madiabu; Ilyas Taufik Abdul Aziz; Supriyono Supriyono; Arie Pratama Putra; Anom Cahyotomo; Hanum Sekar Panglipur (LPPM Universitas Mataram, 2023)
Phytochemical screening and antifungal activity test of jengkol leaf (Archidendron jiringa) extract have been carried out. The purpose of this research is determine secondary metabolite content and antifungal activities of jengkol leaf extract. Extraction of jengkol leaf was conducted with sequential extraction technique with various solvent such as hexane, ethyl acetate and methanol respectively. FTIR characterization of jengkol leaf extract show the presence of O-H, C-H C-O and C=O groups. Based on phytochemical sceening test, jengkol leaf extract contains phenolic, flavonoid, tannin, sterol, and alkaloid compound. Antifungal test was investigated on Candida albicans by disc diffusion methods. Jengkol leaf extract that was obtained from methanol extraction show inhibiton zone to Candida albicans of (1,42 ± 0,16) mm, while extraction with ethyl acetate and hexane aren’t show inhibition zone. Antifungal test result showed that jengkol leaf extract has potential as antifungal agent